Developing a Model of Prevention of Pregnancy Risk Behaviors in Adolescents towards a Process of Community Participation - Pothiboot, Sumontha; Pongtriang, Praditporn; Lumpo, Wayuree (Journal of Research in Nursing-Midwifery and Health Sciences, 2021)
Objective: This participatory action research aimed to develop a model for preventing pregnancy risk behaviors based on a participation process, trial, and evaluation of the model. Methods: This research was comprised three participatory processes. Phase 1 was the development of a protective behavioral pattern against adolescent pregnancy by community participation with 42 cases of community leaders, teachers, health care providers, parents, and adolescents in the community. Phase 2 was a trial phase with 71 parents and adolescents. Phase 3 was the follow-up period with 36 cases of parents and adolescents from the previous phases. The research instrument utilized for data collection included the unstructured interview and observation protocol, with a manual record for preventing risk behaviors in adolescent pregnancy. The content validity of the research instruments was determined by three experts. Results: The interview protocol had a score of 0.78., and a manual record for preventing teenage pregnancy risk behaviors achieved 0.64. The quantitative data were analyzed using basic statistics such as frequencies and percentages. The qualitative data were analyzed by content analysis. Discussion: The research results were as follows: through the process of opening a community forum and perceptive in Phase 1, it is possible to define context-appropriate guidelines for implementing adolescent pregnancy prevention activities, consisting of six steps: 1) Problem analysis, 2) Networking development, 3) Solving concept development, 4) Solving strategy, 5) Behavioral monitoring, and 6) Outcome evaluation. The research findings suggest that further quasi-experimental research of a developed model on controlling and preventing adolescent pregnancy may yield new insights.